Isolation and Characterization of Xanthomonas oryzae isolates from different regions of Midnapore district of West Bengal and their Ecofriendly management by some medicinal plant extracts - Tanushree Tulsian Samanta; Ankita Das; Pradip Samanta (International Journal of Phytomedicine, 2014)
The potential of indigenous medicinal plants as alternative chemical pesticides for controlling bacterial leaf blight (BLB) of rice was tested in the present study. Infected plant samples were collected from five different fields of Purba and Paschim Medinipur, West Bengal. The obtained isolates were subjected to biochemical tests which showed similar results. Xanthomonas oryzae pv. Oryzae, the causal agent of the bacterial leaf blight of rice was characterized through different biochemical tests and assays. Isolates gave dome shaped, yellow colonies on nutrient agar (NA) plates. Gram staining showed that the pathogen is Gram negative and rod shaped, also potassium hydroxide (KOH) test was performed in order to support the results of Gram staining. Endospore staining showed that the isolated pathogen is a non-spore forming bacterium. Starch hydrolysis test, egg yolk reaction, gelatin hydrolysis test and oxidase test gave negative results against the pathogen. Four different and easily available medicinal plant species such as Adhatoda vasica, Lantana camera, Allium sativum and Citrus limon were screened for antibacterial activity against the isolated pathogen. Based on the biochemical responses and also the activity against different plant extracts, it may be concluded that the causal agent is the same for the bacterial leaf blight of rice in the chosen fields of Purba and Paschim Medinipur and there is no significant difference between the pathogenicity and activity of the isolates from the different fields put to test.